2012
DOI: 10.1002/jcb.24126
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanins stimulate protein synthesis in myeloma cell lines

Abstract: Intensive protein synthesis is a unique and differential trait of multiple myeloma (MM) cells. Previously we showed that tetraspanin (CD81, CD82) overexpression in MM cell lines attenuated Akt/mTOR cascades, activated UPR, and caused autophagic death, suggesting breach of protein homeostasis. Here, we explored the role of protein synthesis in the tetraspanin‐induced MM cell death. Contrary to attenuation of the major metabolic regulator, mTOR we determined elevated steady‐state levels of protein in CD81N1/CD82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
(91 reference statements)
0
17
0
Order By: Relevance
“…Recently, dosage effects of protein translation and transport genes are reported for plasma cell leukemia, a cancer closely related to myeloma [31]. Overdrive of translation machines is a feature of cancer cell proliferation [32-34]. Dosage sensitivity of the genes in translation processes indicates their expression levels are not subject to tightly controlled dosage compensation and are susceptible to the influence of copy number alteration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, dosage effects of protein translation and transport genes are reported for plasma cell leukemia, a cancer closely related to myeloma [31]. Overdrive of translation machines is a feature of cancer cell proliferation [32-34]. Dosage sensitivity of the genes in translation processes indicates their expression levels are not subject to tightly controlled dosage compensation and are susceptible to the influence of copy number alteration.…”
Section: Discussionmentioning
confidence: 99%
“…The hypermethylation of their gene promoters contributes to the silencing [32]. Overexpression of CD81-GFP and CD82-GFP fusions in MM cells causes massive autophagic, nonapoptotic death [33,34] by attenuating Akt/mTOR signaling [35], activating the unfolded protein response [34], and stimulating protein synthesis [36]. Notably, overexpression of GFP-CD81 and GFP-CD82 fusions in MM cells reduces cell-matrix adhesion and cell movement [33].…”
Section: Cd82 Solid Tumors and Hematopoietic Malignanciesmentioning
confidence: 98%
“…CD81 is a transmembrane cell surface protein. Some studies have revealed that CD81 expression predicts a poor prognosis for PCM patients . In this study, CD117 and CD81 expression was analyzed in 131 patients who received initial treatment for PCM, and the relationship between CD117/CD81 expression and patient prognosis was further evaluated.…”
Section: Introductionmentioning
confidence: 99%